Hubungan Tingkat Pengetahuan dan Kepatuhan Pemeriksaan Kehamilan Terhadap Kecemasan Pada Ibu Hamil di PMB Bidan Sartika - Suara, Mahyar; Endriyanto, Dimas (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Anxiety is a form of negative emotional state that causes concerns about changes in the mother during pregnancy, fetal development, the upcoming labor process, problems with the mother's psychological readiness, and others. This problem often has a negative impact on the mother and fetus, and has a long-term impact on the child's growth and development (Halil & Puspitasari, 2023). To determine whether there is a relationship between the level of knowledge and compliance with pregnancy check-ups on anxiety in pregnant women at PMB Bidan Sartika in 2024. This study uses a quantitative method with a cross-sectional approach with the Chi-Square test. With a Simple Random Sampling sampling technique that uses primary data obtained from filling out a questionnaire to determine the relationship between the level of knowledge and compliance with pregnancy check-ups on anxiety in pregnant women at PMB Bidan Sartika in 2024. There is no relationship between knowledge and compliance with anxiety in pregnant women at PMB Bidan Sartika in 2024. There was a population in this study of 60 pregnant women patients with a sample of 38 respondents. Based on statistical analysis, it shows that the p-value of knowledge of pregnant women patients is 0.057, the p-value of compliance is 0.550, and the p-value. It is concluded that HO is accepted and Ha is rejected, which means there is no relationship between knowledge and compliance with pregnancy check-ups on anxiety in pregnant women. The results of the study indicate that there is no significant relationship between knowledge, compliance with pregnancy check-ups and anxiety in pregnant women at PMB Bidan Sartika in 2024. It is hoped that this intervention will reduce anxiety levels and improve the quality of pregnant women. Keywords: Knowledge, Compliance, Anxiety of Pregnant Women.  ABSTRAK Kecemasan merupakan wujud dari keadaan emosi negatif yang menimbulkan kekhawatiran perubahan pada ibu selama kehamilan, perkembangan janin, proses persalinan yang akan datang, masalah kesiapan psikologis ibu, dan lain-lain. Masalah ini seringkali menimbulkan dampak negatif bagi ibu dan janin, serta berdampak jangka panjang terhadap tumbuh kembang anak  (Halil & Puspitasari, 2023). Untuk mengetahui apakah ada hubungan tingkat pengetahuan dan kepatuhan pemeriksaan kehamilan terhadap kecemasan pada ibu hamil di PMB Bidan Sartika tahun 2024. Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross sectional dengan uji Chi-Square. Dengan teknik pengambilan sampel Simple Random Sampling yang menggunakan data primer yang didapat dari pengisian kuesioner untuk mengetahui hubungan tingkat pengetahuan dan kepatuhan pemeriksaan kehamilan terhadap kecemasan pada ibu hamil di PMB Bidan Sartika Tahun 2024. Tidak terdapat hubungan antara pengetahuan dan kepatuhan dengan kecemasan pada ibu hamil di PMB Bidan Sartika Tahun 2024. Terdapat populasi dalam penelitian ini sebanyak 60 pasien ibu hamil dengan sampel sebanyak 38 responden. Berdasarkan analisis statistic menunjukkan bahwa nilai p-value pengetahuan pasien ibu hamil 0,057, nilai p-value kepatuhan 0,550, dan nilai p-value. Disimpulkan bahwa HO diterima dan Ha ditolak yang berarti tidak ada hubungan antara pengetahuan, dan kepatuhan pemeriksaan kehamilan terhadap kecemasan pada ibu hamil. Dari hasil penelitian menunjukkan bahwa tidak terdapat hubungan yang signifikan antara pengetahuan, kepatuhan pemeriksaan kehamilan terhadap kecemasan pada ibu hamil di PMB Bidan Sartika Tahun 2024. Diharapkan intervensi ini mengurangi tingkat kecemasan dan meningkatkan kualitas ibu hamil. Kata Kunci: Pengetahuan, Kepatuhan, Kecemasan Ibu Hamil.